Once again: Investigating the identity of the three figures mentioned in Malachi 3:1 - Snyman, Fanie (Verbum et ecclesia, 2006)
The identity of the three figures mentioned in Malachi 3:1 remains an intriguing question for scholars. In this article an overview of the current state of research on this problem is given highlighting the strengths and weaknesses of the different solutions while yet another proposal is made adding some new arguments to existing answers. An overview on the history of research done on this problem can be categorised into three groups: the three figures refer to three different personalities or they all refer to the same person or they refer to two different persons. The conclusion reached is that the three figures mentioned are references to two persons, the one human and the other divine. The messenger is identified as the prophet Malachi.